95 Assessment of on-Arrival Vaccination and Deworming on Stocker Cattle Health and Growth Performance. (1st March 2018) - Wagner, R T; Karisch, B B; Blanton, J R; Woolums, A; Smith, D R; Kaplan, R
Abstract: The study objective was to determine the effect of on-arrival vaccination and deworming on bovine respiratory disease (BRD) incidence, mortality, and performance in newly received stocker cattle. Eighty calves (BW=213.5 ± 9.03 kg), steers (n=23) and bulls (n=57), of sale barn origin were received from an order buyer over 2-day period (d -3 or -2). Bull calves were castrated on arrival and calves were stratified by arrival body weight and fecal egg count (FEC) into 20 pens. Treatments of vaccination (5-way modified live virus BRD and clostridial vaccine, VAC) or not (NOVAC) and deworming (oral fenbendazole and levamisole, DWM) or not (NODWM) were randomly assigned in 2 x 2 factorial arrangement on d 0 to each pen. On d 54 all groups received vaccination with same product. Body weights were measured on d 0, 12, 26, 40, 54, 68, and 82. Feces and blood were collected on arrival and d 0, respectively, along with d 26, 54, and 82. Cattle were observed for clinical signs of BRD and rectal temperature ≥ 40°C. Treatment effects on BRD incidence, mortality, and performance were tested using poison distribution, logistic or linear regression, respectively, using the MIXED procedure of SAS. There were 4, 741 total days at risk and overall incidence density was 5.7 BRD cases per 1, 000 calf days. Overall morbidity was 33.75% with zero mortality. Overall morbidity (20 vs. 13.75%) did not differ ( P >0.10) between DWM and NODWM. Similarly, morbidity (20 vs. 13.75%) between VAC and NOVAC did not differ ( P >0.10). Average daily gain was greater ( P =0.04) for NOVAC (1.56 kg/d) compared to VAC (1.42 kg/d) from d 0 to d 54; however, overall ADG did not differ ( P =0.98) for VAC (1.23 kg/d) and NOVAC (1.23 kg/d). Over entire study ADG was decreased ( P <0.01) for NODWM (1.16 kg/d) compared to DWM (1.29 kg/d) and cattle castrated on arrival (1.15 kg/d) compared to previously castrated (1.31 kg/d). Mean FEC for DWM and NODWM cattle at arrival was 604.1 and 663.8 EPG, respectively. FEC of NODWM decreased over time, and by d 82 FEC of DWM (8.75 EPG) and NODWM (38.3 EPG) did not differ ( P =0.85). Vaccination and deworming on arrival had no effect on BRD incidence. Castration and NODWM at arrival decreased growth performance compared to DWM and previous castration while vaccination at arrival decreased growth performance the initial 54 days. No difference among treatments was observed for growth performance throughout the entire trial.